The effect of contrast temperature water therapy on repeated sprint performance - Hamlin, M. J. (Journal of Science and Medicine in Sport, 2007)
The aim of this study was to compare the effectiveness of two recovery techniques on blood lactate and repeated sprint performance. In a randomised cross-over design 20 junior representative rugby players (aged 19 ± 1 years) were given either contrast temperature water therapy or active recovery after performing a repeated sprint test. The test was then repeated 1 h later to gauge the effects of the two recovery methods on subsequent repetitive sprinting performance. One week later, the two groups were reversed and the testing repeated. The test consisted of ten 40-m sprints with a 30-s turn-around between sprints. Recovery consisted of 6 min slow jogging (6.8 km h-1) for the active recovery group or 6 min of contrast temperature water therapy consisting of three 1-min hip-height immersions in cold water (8-10 °C) alternated with three 1-min hot water (38 °C) showers. Blood lactate concentration and heart rates were measured throughout the testing. Relative to the active recovery group the contrast temperature water therapy group showed a substantial decrease in blood lactate concentration 3 min after the procedure (-2.1 mmol L-1, 95% confidence limits, ±1.8 mmol L-1), and substantially lower heart rates both during the procedure (-9.1 ± 8.7 min-1) as well as 1 h later during the second set of sprints (-11.7 ± 8.6 min-1). Effects of recovery group on repeated sprint performance were small to trivial and unclear. Compared to active recovery, contrast temperature water therapy decreases blood lactate concentration and heart rate but has little effect on subsequent repetitive sprinting performance.